2012
DOI: 10.1007/s10834-012-9326-z
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure and Children’s Education Outcome: Evidence from Uruguay

Abstract: As the developed world has experienced a shift away from the traditional two-biological parent family, scholars have sought to understand how children are faring in non-traditional homes. Debate has arisen over assertions that children from non-traditional families do less well in school. Concerns about selection issues as well as a paucity of cross-cultural evidence, have led some scholars to question the influence of family structure on educational attainment.Using data from the 2006 Uruguayan household surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
2
12
0
2
Order By: Relevance
“…Some authors defend the notion that family structure is itself the cause of poorer performance (Cid & Stokes, 2013;Francesconi et al, 2010;Frisco, Muller, & Frank, 2007). By contrast, other authors provide evidence that this association is mediated by other factors simultaneously correlated with family structure and academic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors defend the notion that family structure is itself the cause of poorer performance (Cid & Stokes, 2013;Francesconi et al, 2010;Frisco, Muller, & Frank, 2007). By contrast, other authors provide evidence that this association is mediated by other factors simultaneously correlated with family structure and academic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We then unpack potential reasons these two research streams reach different conclusions-and ask whether their conclusions are actually that different in the end. While most of the research we discuss here focuses on people in the United States, we note that similar patterns are observed in other countries (e.g., Bjorklund, Ginther, & Sundstrom, 2007;Cid & Stokes, 2011;Steele, Sigle-Rushton, & Kravdal, 2009). Finally, we discuss holes in our knowledge about the relationships between family structure and adult opportunities and attainment, and we outline opportunities for research that could help fill those holes.…”
mentioning
confidence: 56%
“…Although mainly dominated by the West, (Cid and Stokes 2013, Uruguay;Monserud and Elder 2011;Martin 2012, USA;Frisco et al 2007, USA), this body of literature has consistently shown that children in 'intact' families have better outcomes across different educational indicators. When examining the effect of family structure on school dropout and falling behind, Cid and Stokes (2013) found that children raised in non-traditional families (without both biological parents) had negative outcomes, with more adverse effects for girls. Others have also shown that growing up in single-parent families might reduce the chances of completing high school and enrolling in post-secondary education (Monserud and Elder 2011;Astone and McLanahan 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is assumed that children from single-headed or non-resident parent families are likely to suffer from economic vulnerability as well as structural deficiency related to lack of parental involvement in their welfare (Monserud and Elder 2011;Martin 2012). On the contrary, co-resident parents are seen as more attractive in transmitting socioeconomic resources to their children (Cid and Stokes 2013).…”
Section: Introductionmentioning
confidence: 99%